Hubungan Tingkat Pengetahuan Ibu Dan Tingkat Pendidikan Ibu Dengan Terjadinya Karies Gigi Pada Anak Usia Pra Sekolah - Ermawati Ermawati; Yunlia Vidiarti; Shelly Ayu Andesty; Andi Tenri; Vip Paramarta (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Caries is a disease of hard tooth tissue, namely enamel, dentin and cementum, which is caused by the activity of microorganisms in fermentable carbohydrates. Federation Dental International (FDI) and WHO target that at least 50% of children aged 5-6 years should be free from dental caries in every country. The results of the 2018 Basic Health Research (Risksdas) show that the prevalence of cavities in early childhood is still very high, namely around 93%. This means that only 7% of Indonesian children are free from dental caries (Ministry of Health, 2021). This article aims to determine the relationship between the level of knowledge and the mother's education level with the occurrence of dental caries in pre-school children at the Bukit Damai PAUDHI Kindergarten, Maluk District. The research method for this article is an analytical survey with a cross-sectional approach. The population is parents, guardians of students at HI BukitDamai PAUD Kindergarten in Maluk District, Kab. West Sumbawa, NTB as many as 20 parents/guardians of students. The results of this study showed that there was a relationship between the level of maternal knowledge and the occurrence of dental caries in pre-school children with a p-value of 0.001 (<0.05). Also, there is a significant relationship between maternal education level and the occurrence of dental caries in pre-school children with a p-value of 0.011 (<0.05). It is hoped that there will be a need for intensive dental and oral health checks on pre-school aged children, as well as providing counseling to mothers of toddlers, especially pre-school aged children.